Probiotic in feed for tilapia cultivated in treated domestic sewage effluent - Ferreira, Antônio Hosmylton Carvalho; Lopes, João Batista; Alencar Araripe, Maria de Nasaré Bona de; Monteiro, Cleto Augusto Baratta; Andrade, Francisco Teixeira; Kimpara, Janaina Mitsue (Comunicata Scientiae, 2016)
The bioimpedance is a method used to estimate humans and animals body composition, characterized by determining the value of the phase angle. This study aimed to estimate the fish condition through electrical bioimpedance technique and evaluate the performance of Nile tilapia grown in sewage water treated with the addition of probiotic (Bacillus licheniformis, Bacillus cereus and Bacillus subitillis and yeast - Saccharomyces cerevisiae and boulardi) in diets. For the experiment, 360 fingerlings were used with initial average weight of 2.91 ± 0.37 g and initial average length of 3.30 ± 0.27 cm, distributed in a completely randomized design with three treatments and six repetitions of 20 fish each. Treatments consisted of: PRO1 - fish grown in clean water; RO2 - fish grown in wastewater; PRO3 - fish grown in wastewater + probiotic added to the feed. All animals were fedto apparent satiety. Tilapia that were submitted to the health challenge (wastewater) presented phase angle less than 15°. Fulton´s K value was higher for the group treated with sewage water. The wastewater does not present conditions for a good crop and a good development of the fish, regardless the probiotic supplementation and the measurement method of health status used. The probiotic strains did not led to an improvement of fish performance and survival.